Cast production and NIR spectra signatures of Aporrectodea caliginosa fed soil with different amounts of half-decomposed Populus nigra litter - Zhang, C; Langlest, R; Velásquez, E.; Pando, A; Brunet, D.; Dai, J.; Lavelle, Patrick M. (Springer, 2009)
Sub-adult individuals of Aporrectodea caliginosa were incubated for 16 weeks under laboratory cultures in a soil treated with 0%, 10% or 50% of a Populus nigra half-decomposed leaves, respectively. Growth was maximum in the 50% organic matter treatment and cocoon production occurred. Average soil ingestion rates decreased from 1.56 g/g?1 fresh weight of worm per day?1 in control soil to 1.17 and 0.5 g, respectively, in treatments with 10% and 50% half-decomposed litter. Surface casts never comprised more than 10% of total cast production. Near-infrared spectrometry (NIRS)signatures of digested and non-ingested soil significantly differed and showed a rather constant effect of digestion, independent of the organic matter content (p?<?0.01). These results confirm the value of NIRS spectral signatures as indicators of the origin of soil aggregates and biological processes involved in soil aggregation